2021
DOI: 10.1002/art.41625
|View full text |Cite
|
Sign up to set email alerts
|

From Diagnosis to Prognosis: Revisiting the Meaning of Muscle ISG15 Overexpression in Juvenile Inflammatory Myopathies

Abstract: Objective. Juvenile idiopathic inflammatory/immune myopathies (IIMs) constitute a highly heterogeneous group of disorders with diagnostic difficulties and prognostic uncertainties. Circulating myositis-specific autoantibodies (MSAs) have been recognized as reliable tools for patient substratification. Considering the key role of type I interferon (IFN) up-regulation in juvenile IIM, we undertook the present study to investigate whether IFN-induced 15-kd protein (ISG-15) could be a reliable biomarker for strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
(49 reference statements)
2
21
0
Order By: Relevance
“…However, steroid resistance in some patients results in poor prognosis and warrants new therapeutic strategies [ 28 ]. IFN-related endothelial injury and Janus kinase (JAK) inhibition has emerged as a novel therapeutic strategy in difficult-to-treat cases [ 1 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, steroid resistance in some patients results in poor prognosis and warrants new therapeutic strategies [ 28 ]. IFN-related endothelial injury and Janus kinase (JAK) inhibition has emerged as a novel therapeutic strategy in difficult-to-treat cases [ 1 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…ISG15 is an IFN- α / β -inducible, intracellular ubiquitin-like protein. Related studies have shown that the level of ISG15 is negatively correlated with the severity of muscle histological damage and positively correlated with exercise capacity (CMAS, MMT) [ 36 , 37 ]. In addition, for the diagnosis of juvenile DM, the expression of muscle ISG15 is closely related to juvenile DM and may be a potential biomarker for the diagnosis of juvenile DM [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown that the level of ISG15 is negatively correlated with the severity of muscle histological damage and positively correlated with exercise capacity (CMAS, MMT) [ 36 , 37 ]. In addition, for the diagnosis of juvenile DM, the expression of muscle ISG15 is closely related to juvenile DM and may be a potential biomarker for the diagnosis of juvenile DM [ 37 ]. In recent years, the description of ISG15 as a central participant in host antiviral response has been widely accepted, and ISG15 could protect and limit the damage to human tissues caused by the viral response through the participation and regulation of the type I interferon signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In their report, Dubowitz and colleagues discuss their negative staining results of interferons alpha, beta and gamma that had been mentioned to occur by Isenberg 1986. Nowadays we know that it is feasible to detect type I interferon-related gene expression in jDM muscle with certain modern techniques even in different serological subtypes of jDM [27] . Victor Dubowitz' pioneering work on MHC class I expression in DMD and in child inflammatory myopathy as well as in other neuromuscular diseases dates from 1984 and was published in the Lancet [28] .…”
Section: Morphologymentioning
confidence: 99%
“…The levels of expression of ISGs that promote IFN-I signalling (IFIH1, DDX58) were remarkably similar amongst JDM patients whatever the MSAs. Conversely, an inverse correlation between the expression levels of the IFN-I signalling regulator ISG15 in the muscle and the severity of muscle involvement were identified [27] . These results suggest that the individual ability of muscle resident cells to control the response to IFN-I is a key factor for determining disease progression.…”
Section: Article In Pressmentioning
confidence: 99%